Analysis Effect of Profitability, Debt Policy, and Dividends Policy to Corporate Values an Empirical Study from Indonesian Manufacturing Companies - Aboalayoon, Ahmed A. Amer; , M. Farid Wajdi, Ph.D (2014)
The purpose of this study was to analyze the factors that affect the value of the company at the companies listed in Indonesia Stock Exchange (IDX). Factors affecting the value of the company in this study are profitability, debt policy and dividend policy on firm value. The sample in this study is a manufacturing company listed on the Stock Exchange 2010-2012. This study used purposive sampling method. Source data were obtained from published financial statements of the company by the Indonesian Stock Exchange (BEI) in 2010-2012, with a sample size of 30 manufacturing companies. The analysis technique used is multiple regression analysis. The results showed that only profitability significantly and positively related to firm value, while debt policy and dividend policy has no significant effect on firm value.